Mechanisms of sexually transmitted infection‐induced inflammation in women: implications for HIV risk - Ruth S. Mwatelah; Lyle R. McKinnon; Cheryl Baxter; Quarraisha Abdool Karim; Salim S. Abdool Karim (2019)
Abstract Introduction Globally, sexually transmitted infections ( STI ) affect >300 million people annually, and are a major cause of sexual and reproductive health complications in women. In this commentary, we describe how STI s interact with the immune and non‐immune cells, both within and below the cervicovaginal mucosal barrier, to cause inflammation, which in turn has been associated with increased HIV acquisition risk. Discussion STI s have a major impact on the female genital mucosa, which is an important biological and physical barrier that forms the first line of defence against invading microorganisms such as HIV . Pattern recognition of STI pathogens, by receptors expressed either on the cell surface or inside the cell, typically triggers inflammation at the mucosal barrier. The types of mucosal responses vary by STI , and can be asymptomatic or culminate in the formation of discharge, ulcers and/or warts. While the aim of this response is to clear the invading microbes, in many cases these responses are either evaded or cause pathology that impairs barrier integrity and increases HIV access to target cells in the sub‐mucosa. In addition, innate responses to STI s can result in an increased number of immune cells, including those that are the primary targets of HIV , and may contribute to the association between STI s and increased susceptibility to HIV acquisition. Many of these cells are mediators of adaptive immunity, including tissue‐resident cells that may also display innate‐like functions. Bacterial vaginosis ( BV ) is another common cause of inflammation, and evidence for multiple interactions between BV , STI s and HIV suggest that susceptibility to these conditions should be considered in concert. Conclusions STI s and other microbes can induce inflammation in the genital tract, perturbing the normal robust function of the mucosal barrier against HIV . While the impact of STI s on the mucosal immune system and HIV acquisition is often under‐appreciated, understanding their interactions of the infections with the immune responses play an important role in improving treatment and reducing the risk of HIV acquisition. The frequent sub‐clinical inflammation associated with STI s underscores the need for better STI diagnostics to reverse the immunological consequences of infection.